The Role of Mass Media in Shaping Public Discourse on Age Limits in Job Recruitment in Indonesia - Andika Witono; Kezia Descita Ryzan; Ryan Ichiro Martohasian (Institut Komunikasi dan Bisnis LSPR, 2025)
In recent years, age limitations in job recruitment have emerged as a highly debated issue in Indonesia, attracting significant attention. Many Indonesian companies set age ceilings for job applicants, commonly setting limits around 25-30 years of age. This practice has caused growing frustration among job seekers, prompting widespread public discourse across various media platforms. The Ministry of Manpower(Kemnaker) as the responsible authority, aims to promote a productive, competitive, and prosperous workforce, yet controversies related to age-based recruitment policies persist. Media outlets, ranging from online news portals to social media platforms, play a critical role in shaping the discussion around age discrimination. This study employs content analysis to investigate how the Indonesian mass media frames this issue, identifying prevailing narratives, biases, and their potential negative public emotions and policy development on public opinion and policy development. The significance of this research lies in its exploration of the media's power in providing information and governmental responses to employment equity. Through qualitative approach and using Robert Entman’s framing theory to analyze a comprehensive evaluation of media portrayals, this study contributes insights into the complexities surrounding age-based recruitment practices, emphasizing the importance of inclusive employment policies for Indonesia's workforce sustainability.